2010 IEEE International Conference on Software Maintenance 2010
DOI: 10.1109/icsm.2010.5609672
|View full text |Cite
|
Sign up to set email alerts
|

Test generation via Dynamic Symbolic Execution for mutation testing

Abstract: Mutation testing has been used to assess and improve the quality of test inputs. Generating test inputs to achieve high mutant-killing ratios is important in mutation testing. However, existing test-generation techniques do not provide effective support for killing mutants in mutation testing. In this paper, we propose a general test-generation approach, called PexMutator, for mutation testing using Dynamic Symbolic Execution (DSE), a recent effective test-generation technique. Based on a set of transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 41 publications
1
72
0
2
Order By: Relevance
“…Mutation adequacy is more stringent than statement or branch coverage [9]. There has been much research into test generation for mutation adequacy [35] [36] [37] [38], but our work is the first to optimise and select subdomains from which efficient test cases can be sampled.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation adequacy is more stringent than statement or branch coverage [9]. There has been much research into test generation for mutation adequacy [35] [36] [37] [38], but our work is the first to optimise and select subdomains from which efficient test cases can be sampled.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we determine all the dominated mutant branches by the above statistical approach. The automated analysis of the dominance relation between mutant branches will be a significant research task in our near future work, and related work such as Kurtz et al [46], Kintis and Malevris [52], Offutt and Pan [53], and Zhang et al [54] will be of great help in achieving this goal. Furthermore, we find that different branches have different numbers of dominated branches.…”
Section: Discussionmentioning
confidence: 99%
“…Jia and Harman recently surveyed mutation analysis for programs and other software engineering artifacts [16]. One point from their survey is that automatic test generation for mutation analysis, a key step towards bringing mutation analysis to standard industrial practice, has recently been the subject of renewed attention in the literature [12,31,32,39]. The statement-level operators have been fairly stable since the Mothra project [26], with the only major change being from the selective operator study [33], where it was found that using five Mothra mutation operators would yield tests that killed most other mutants.…”
Section: Improving Logic-based Testing With Mutationmentioning
confidence: 99%